1996
DOI: 10.2135/cropsci1996.0011183x003600050030x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers Associated with Water Use Efficiency and Leaf Ash in Soybean

Abstract: Water use efficiency (WUE) is an important trait that has been associated with drought tolerance of crop plants, and leaf ash (LASH) generally related to WUE. A restriction fragment length polymorphism (RFLP) map was constructed from a soybean [Glycine max (L.) Merr.] population of 120 F4-derived lines from a cross of'Young' × P1416937. The purpose of this research was to identify quantitative trait loci (QTL) associated with WUE and LASH in 36-d-old, greenhouse-grown plants. The experimental design was a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 0 publications
5
75
0
1
Order By: Relevance
“…This region is adjacent to RM339-RM342, where DRI and CT (canopy temperature)-related QTLs [20] and RGDD-related QTL are positioned [21]. One QTL controlling kernelw/d was located on Chr4 and this region neighbors the region (RM142-RM119) where one QTL controlling kernelw is positioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region is adjacent to RM339-RM342, where DRI and CT (canopy temperature)-related QTLs [20] and RGDD-related QTL are positioned [21]. One QTL controlling kernelw/d was located on Chr4 and this region neighbors the region (RM142-RM119) where one QTL controlling kernelw is positioned.…”
Section: Discussionmentioning
confidence: 99%
“…The QTL with the largest additive effect was from aus rice and was colocalized with QTLs for leaf length, tiller number, and nitrogen content [8]. Mian et al [20] conducted QTL mapping on the WUE of beans with 120 F 4 lines from the cross Young × PI416937 and detected four QTLs accounting for 38% of phenotypic variation.…”
mentioning
confidence: 99%
“…There are reports of work with Triticum aesvum L. (Zhang, 1998;Richards et al, 2002;Sheshshayee et al, 2003;Tuberosa, 2003Tuberosa, , 2005, Triticum vulgare L. (Handley et al, 1994;Teulat et al, 2002;Ellis et al, 2002;Molnar et al, 2007), Oryza sativa L. (Fischer et al, 2003), Zea mays L. (Banziger et al, 2000), Gossypium spp. (Warwick et al, 2005;Saranga et al, 2001), Glycine max L. (Mian et al, 1996(Mian et al, , 1998, Lycopersicum esculentum Mill (Martin et al, 1989;Lin et al, 2002), and Brassica oleracea (Hall et al, 2005). Compared with other methods for saving water, breeding new crop varieties with a high yield and WUE as well as drought-resistance has the following merits: less investment by the grower, greater uptake through low costs of technology transfer, sustainable efficiency; and more potential exploitation.…”
Section: Review Articlementioning
confidence: 99%
“…This response would depend on the maintenance of constant concentration of minerals in the transpiration stream. Mian et al, (1996) combined leaf ash and RFLP technologies to identify quantitative trait loci (QTL) associated with WUE in soybean. They found that six RFLP markers were associated with WUE p , of the six, one is on LG15 (G), two are on LG17 (H), and three are on LG 18(J); marker cr497-1 (LG18) explained the largest amount of variation (13.2%) of all markers, and the parent "Young" allele at this locus contributes to the greater WUE of progeny lines.…”
Section: Wue Gene Locationmentioning
confidence: 99%
“…Responses to environmental stresses including salt tolerance (Guo et al 1998, Qin et al 2000, iron deficiency , Lin et al 1998, water use efficiency (Mian et al 1996) and chlorimuron ethyl sensitivity (Mian et al 1997) were genetically analyzed.…”
Section: Genetic Mapping Of Trait Locimentioning
confidence: 99%